Genome-wide DNA methylation patterns in LSH mutant reveals de-repression of repeat elements and redundant epigenetic silencing pathways - Yu, Weishi; McIntosh, Carl; Lister, Ryan; Zhu, Iris; Han, Yixing; Ren, Jianke; Landsman, David; Lee, Eunice; Briones, Victorino; Terashima, Minoru; Leighty, Robert; Ecker, Joseph R.; et al. (Genome Research, 2014)
Cytosine methylation is critical in mammalian development and plays a role in diverse biologic processes such as genomic imprinting, X chromosome inactivation, and silencing of repeat elements. Several factors regulate DNA methylation in early embryogenesis, but their precise role in the establishment of DNA methylation at a given site remains unclear. We have generated a comprehensive methylation map in fibroblasts derived from the murine DNA methylation mutant Hells−/− (helicase, lymphoid specific, also known as LSH). It has been previously shown that HELLS can influence de novo methylation of retroviral sequences and endogenous genes. Here, we describe that HELLS controls cytosine methylation in a nuclear compartment that is in part defined by lamin B1 attachment regions. Despite widespread loss of cytosine methylation at regulatory sequences, including promoter regions of protein-coding genes and noncoding RNA genes, overall relative transcript abundance levels in the absence of HELLS are similar to those in wild-type cells. A subset of promoter regions shows increases of the histone modification H3K27me3, suggesting redundancy of epigenetic silencing mechanisms. Furthermore, HELLS modulates CG methylation at all classes of repeat elements and is critical for repression of a subset of repeat elements. Overall, we provide a detailed analysis of gene expression changes in relation to DNA methylation alterations, which contributes to our understanding of the biological role of cytosine methylation.
10.1101/gr.172015.114